2017
DOI: 10.3389/fpls.2017.00053
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Biochemical and Transcriptomic Effects of a Locally Applied Heat Treatment on Developing Cabernet Sauvignon Grape Berries

Abstract: Reproductive development of grapevine and berry composition are both strongly influenced by temperature. To date, the molecular mechanisms involved in grapevine berries response to high temperatures are poorly understood. Unlike recent data that addressed the effects on berry development of elevated temperatures applied at the whole plant level, the present work particularly focuses on the fruit responses triggered by direct exposure to heat treatment (HT). In the context of climate change, this work focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
146
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(164 citation statements)
references
References 156 publications
(214 reference statements)
16
146
2
Order By: Relevance
“…As such Gaiotti et al (2018) emphasize the beneficial effects of cool nights on anthocyanins accumulation. Similar results were obtained by transcriptomic heat stress studies that showed that high temperature is unfavorable for anthocyanin synthesis (Lecourieux et al, 2017;Rienth et al, 2014b;Rienth et al, 2016). Interestingly such effects are most pronounced during the short (24h lasting) véraison phase, where the berry seems to be most vulnerable to abiotic stresses (Rienth et al, 2014b).…”
Section: Effect Of Hydraulic Structure Light and Temperature On Transupporting
confidence: 82%
“…As such Gaiotti et al (2018) emphasize the beneficial effects of cool nights on anthocyanins accumulation. Similar results were obtained by transcriptomic heat stress studies that showed that high temperature is unfavorable for anthocyanin synthesis (Lecourieux et al, 2017;Rienth et al, 2014b;Rienth et al, 2016). Interestingly such effects are most pronounced during the short (24h lasting) véraison phase, where the berry seems to be most vulnerable to abiotic stresses (Rienth et al, 2014b).…”
Section: Effect Of Hydraulic Structure Light and Temperature On Transupporting
confidence: 82%
“…Finally, no effects on anthocyanin concentration and profile were found as biosynthesis was not yet triggered in the berries when HE1 was applied. This is in agreement with other studies on Cabernet Sauvignon reporting that anthocyanins were not affected by high temperature when applied during early berry development (Buttrose et al, 1971;Lecourieux et al, 2017).…”
Section: Physiology and Composition Parameters Affected By The Firstsupporting
confidence: 93%
“…Several experiments have already studied berry development and/or metabolite accumulation, but most short-term whole-vine heating treatments were under limited ultra-violet (UV) radiations, e.g. polycarbonate enclosures Sweetman et al, 2014), in growth chambers without UV supplement (Greer and Weston, 2010;Sweetman et al, 2014) or in green houses built with glass or plastic filtering most natural light and UV (Lecourieux et al, 2017;Majer and Hideg, 2012;Pillet, 2011). Systems allowing a more natural UV environment such as open-top chambers have been developed, but have mainly been used to study an increase in long-term average temperature (+ 1-3°C) during several months or the whole grape growing season de Rosas et al, 2017;Sadras and Soar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While such treatment during 10–20 weeks after anthesis reduced the amount of incoming photosynthate partitioned to citrate and increased that allocated to sucrose in fruits. Lecourieux et al () reported a significant decrease in the content of malic acid in grape ( Vitis vinifera L. cv. Cabernet Sauvignon) as heat treatment was applied on bunches during stage of either veraison (50% of berries turning to a visible red color) or middle‐ripening (80 days after fruit set), but no impact in its concentration in those heated as stage of middle‐green (30 days after fruit set) was recognized.…”
Section: Organic Acidsmentioning
confidence: 99%